Critical success factors in the management of ideas as an essential component ofi nnovation and business excellence - Santos, Gilberto (2018)
Purpose- This research aims to focus on the idea management system(IMS)with the main purpose of identifying and describing the factors that promote success in managing ideas,grounde don the analysis of cases tudies. Design/methodology/approach – The method used consists of a case study and semi-structured interviews with those directly responsible for the management of ideas from four companies, which are presentedinthispaper. Findings – The main ﬁndings, critical for the success of an IMS, are as follow: the involvement of top management, evidence of results, establishment of goals and objectives, dissemination of good results, willingness to share and develop ideas, complete transparency in the management of ideas, maintenance of dynamicandproactiveattitudesandmainlyrecognition.Allhavebeendescribed. Research limitations/implications – This work presents a preliminary framework for further research toward the study of CSFs inherent to IMSs that is still bound by the limited number of case studies presented. Further research should be undertaken to broaden and consolidate the presented CFSs and their pertinence. Originality/value – This study, although limited to four case studies, presents conclusive results that support managers of suggestion systems/IMSs in improving or deploying such systems. The main factors wereidentiﬁedanddescribed.Theycancontributetotheeffectivenessofemployeesuggestionsystem.Itcan be reasoned from this investigation that the contributions from employees toward the success of a company leadstoexcellenceinbusiness.